Correction: Self-assembled fibrillar networks comprised of a naturally-occurring cyclic peptide—LOB3. Issue 24 (7th April 2020) - Rogers, M. A.; Feng, Q.; Ladizhansky, V.; Good, D. B.; Smith, A. K.; Corridini, M.; Grahame, D. A. S.; Bryksa, B. C.; Jadhav, P. D.; Sammynaiken, S.; Lim, L.-T.; Guild, B.; et al.
Abstract : Correction for 'Self-assembled fibrillar networks comprised of a naturally-occurring cyclic peptide—LOB3' by M. A. Rogers et al., RSC Adv., 2016, 6, 40765–40776.